Use of the nonavalent HPV vaccine in individuals previously fully or partially vaccinated with bivalent or quadrivalent HPV vaccines. Issue 6 (3rd February 2016) - Van Damme, Pierre; Bonanni, Paolo; Bosch, F. Xavier; Joura, Elmar; Krüger Kjaer, Susanne; Meijer, Chris J.L.M.; Petry, Karl-Ulrich; Soubeyrand, Benoit; Verstraeten, Thomas; Stanley, Margaret
Abstract: With the availability of the nonavalent human papillomavirus (HPV) vaccine, vaccinees, parents and healthcare providers need guidance on how to complete an immunization course started with the bi- or quadrivalent vaccine and whether to revaccinate individuals who have completed a full immunization course with the bi- or quadrivalent vaccine. To answer these questions three parameters should be considered: age at the start of vaccination (9 to 14 years of age versus 15 years and older, the cut-off for 2 or 3 doses schedule), the number of doses already received and the time interval between doses. Based on a number of scenarios, we propose that the 9-valent vaccine can be used to complete an incomplete vaccination regimen or might be added to a previous completed schedule to extend protection.